New β-Hydroxy Acylsilane-Derived Building Blocks and Their Use in the Synthesis of Oxygen-Containing Heterocycles - Murthy, Akondi Srirama; Roisnel, Thierry; Chandrasekhar, Srivari; Grée, René (Synlett, 2013)
Starting from easily accessible β-hydroxy acylsilanes, several 1C-, 2C- and 3C-extension reactions have been developed to efficiently afford five new functionalized building blocks, which have been used for the preparation of several five- and six-membered lactones.
Keywords: acylsilanes; lactones; aldols; silyl cyanohydrins; silyl enol ether; nucleophilic additions